The Implementation of Podcast Media for Listening Skills Learning Medium of Class XI Student in SMAN 1 Tumpang - Riddel Irsan Mambrisauw (Universitas Negeri Malang, 2020)
This article was conducted with the aim of describing the learning process of applying Podcast media as a learning medium to train the listening skills of class XI language SMAN 1 Tumpang and also to determine student responses to Podcast media. This research method uses descriptive qualitative method and the source of the data in this study were the students of class XI Language, totaling 20 people on German subjects with the theme Essen und Trinken which is done online via WhatsApp group and Google Form. The data on the application was obtained through questionnaires and field note instrument. The results of this study indicate that the application of Podcast media in learning goes well, students feel helped in practicing listening skills. Student responses to the application of Podcast media showed positive results. Through the application of Podcast media, students get new vocabulary on the theme Essen und Trinken.